An Unusual Cause of Enthesopathy of the Bicipital Tuberositas of the Radius: Screw Irritation. Issue 4 (December 2013) - Isik, Cengiz; Cakici, Husamettin; Cagri Kose, Kamil; Akpinar, Fuat
Abstract Background: A 36-year-old woman was suffering from a right forearm ulna-radius diaphysis displaced fracture and a non-displaced fracture of the radius neck. Open reduction and internal fixation with screws and a plate for the ulna and radius diaphysis fractures and a long-arm plaster splint treatment was performed. Findings: Four months later, the patient presented with pain, swelling, and restricted mobility on the antecubital side of the right forearm. Radiography showed that the screw which was used for ulna fixation caused enthesopathy of the neighboring bicipital tuberosity of the radius. Removal of the screw improved the symptoms and angular degree of pronation-supination movements from 20° to 70°. Two years after screw removal, radiography showed resolution of enthesopathy of the radius bicipital tuberosity. Conclusions: When inserting a screw for ulna and radius diaphysis fractures, maximum care must be taken to avoid screw irritation of the bicipital tendon enthesis. When this complication does occur, removal of the causative screw may completely solve the problem.